A Comprehensive Review of Hydraulic Systems in Aerospace and Construction Engineering - Kumar, Sree Biddut; Hossem, Md Saim; Sayed, Abu (Control Systems and Optimization Letters, 2024)
This paper provides a thorough examination of hydraulic systems used in construction and aerospace, emphasizing new developments and their vital functions in contemporary engineering. In the aircraft industry, where dependability at high altitudes is critical, hydraulic systems are essential for precise control over landing gear, flying surfaces, and brake systems. Fly-by-wire technology and advancements in lightweight materials, such carbon fiber-reinforced plastics, have greatly improved system efficiency and decreased mechanical complexity, satisfying the exacting aerospace standards for accuracy, weight efficiency, and dependability. Hydraulic systems provide the force required for heavy lifting and earthmoving operations in a variety of settings, powering vital pieces of equipment such as excavators, cranes, and loaders in the construction industry. Performance, fuel economy, and safety have all increased as a result of recent developments, such as digital automation and energy-efficient designs. For instance, more automation and accuracy are now possible with electro-hydraulic controls, which lowers human effort and increases productivity on construction sites. Each sector's unique problems are also covered in this analysis, such as fluid dependability in harsh environments, system complexity, thermal management, and environmental issues including energy efficiency and fluid leakage. Future trends are examined in the assessment's conclusion, with a focus on sustainable practices such energy-efficient designs and biodegradable hydraulic fluids. By focusing on these fields and developments, this research shows how hydraulic systems continue to propel industrial development, adjusting to intricate needs and advancing engineering applications' technical capabilities.